Nutritional Value of Mackerel Fish Flour (Rastrelliger Sp.) Wet Noodles Fortified with Vegetable Flour - Febry, Ayu Bulan; Ntau, Liean A; Bami, Mahyudin; Hadi, Novian Swasono (Media Gizi Indonesia, 2023)
Wet noodles available on the market are often lacking in adequate nutrition, with higher carbohydrates, lower protein, and fewer vitamins. Thus, develop a healthy, economical, and nutritious wet noodles using local ingredients is needed. The study aimed to investigate the enhancement of nutritional value in wet noodles by fortifying them with vegetable flour and mackerel flour. The study useda true experimental design with a posttest-only control group. The design used a complete randomized design consisting of three treatments and four replications. The three treatments were as follows: F0 (wet noodles with fish flour increased by 10 grams of vegetable flour); F1 (wet noodles with fish flour increased by 15 grams of vegetable flour);and F2 (wet noodles with fish flour increased by 20 grams of vegetable flour). The researchers analyzed the nutritional composition of the noodles, focusing on carbohydrates, proteins, fats, and iron. The findings of the study showed that the carbohydrate content in the three treatments of wet noodles with increased vegetable flour ranged from 14.3% to 16.7%. The protein content in the treatments ranged from 8.61% to 9.22%. The fat content varied from 2.62% to 2.9%. Moreover, the iron content in the treatment of wet noodles with increased vegetable flour ranged from 22.08 mg/kg to 25.76 mg/kg. The result of the ANOVA statistical test showed that there was a significant difference in the addition of vegetable flour to the iron content of mackerel meal wet noodles.